Webtoon Sebagai Media Edukasi Akan Dampak Manusia Terhadap Makhluk Hidup dan Lingkungan Sekitar - Winona Nathania Boenadhi; Shienny Megawati Sutanto (Jurnal Vicidi, 2019)
Destruction to nature due to consumption and behavior of human life have occurred everywhere. There are still many people who do not really realize that humans’ destructive actions, greed and lifestyles greatly affect the surrounding ecosystem and environment. One of the common examples is the use of plastic waste that still tends to be large, thus threatening the lives of living things such as sea turtles and other sea creatures (for eating plastics accidentally). Therefore, to increase public awareness of human impacts on the environment, web comics are designed to educate readers about the issues raised in this study. The media webtoon was chosen as the media for educationg people about human impacts on ecosystems and the environment, as webtoon can be accessed by anyone online. This research was conducted with the aim of increasing public awareness of the impact of humans on other living things, ecosystems and the surrounding environment. It is hoped that with the design of this educational webtoon, the public can be more aware of the problem of human impacts on ecosystems and the environment, and encourage people to take actions to live more environmentally friendly.